STUDI KOMPARATIF PRODUKTIVITAS JERUK BERDASARKAN KARAKTERISTIK, KOMPETENSI, DAN MOTIVASI PETANINYA - Elly Rasmikayati; Tuti Karyani; Bobby Rachmat Saefudin (Universitas Galuh, 2023)
Horticultural agriculture subsector has a role in improving public health through improved nutrition, including as a source of vitamins. One of the horticultural commodities which is superior in its production is citrus. One of citrus production centers in Sumatra is Simalungun Regency, North Sumatra. The yield of citrus farming in Simalungun Regency is actually quite high, but when entering the dry season the production of citrus will drop dramatically. In addition, seasonal changes can sometimes reduce the quality of citrus, although indirectly. The purpose of this study was to analyze the characteristics, competence and motivation of citrus farmers in Simalungun Regency and to comparing citrus productivity based on the characteristics, competence and motivation of the farmers. The research data is 100 respondents in size. The method used for data analysis is descriptive analysis, one way anova and LSD Fisher. The results of the study found that the majority of citrus farmers in Simalungun Regency, North Sumatra were male with a total of 64 people, aged over 27 years, had a land area of under 2.5 hectares, had secondary education, namely SMA-D3, with experience over 10 years in farming. oranges, have high motivation, and have citrus productivity levels that vary in the range of 5000-30,000 kg/ha. The results of the comparative analysis can be concluded that there are significant differences in citrus productivity among groups of farmers classified based on level of education, land tenure and competency. Whereas in the classification of farmer groups based on experience and motivation, the productivity is not different.